2022
DOI: 10.17650/1726-9776-2022-18-2-39-57
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life outcomes in patients with advanced renal cell carcinoma treated with lenvatinib plus pembrolizumab or everolimus versus sunitinib (CLEAR): a randomised, phase 3 study

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Comparative evaluation of various models in the training and validation cohorts. surgery (29,30). Therefore, accurate prediction of patient prognosis and risk of RCC patients is an urgent problem.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative evaluation of various models in the training and validation cohorts. surgery (29,30). Therefore, accurate prediction of patient prognosis and risk of RCC patients is an urgent problem.…”
Section: Discussionmentioning
confidence: 99%
“…В CLEAR в большинстве случаев пациенты уходили с терапии сунитинибом на иммунотерапию, более половины в группе ленватиниба с пембролизумабом -на антиангиогенную терапию, что оказало влияние на результаты. Не отмечено новых сигналов безопасности, связанных с лечением [1,14,15]. Подгрупповой анализ качества жизни (КЖ) пациентов продемонстрировал лучшую переносимость комбинации ленватиниба с пембролизумабом в сравнении с монотерапией сунитинибом, по показателям КЖ, связанного со здоровьем (Health-Related Quality of Life, HRQoL), а также по симптомам заболевания [14].…”
Section: ленватиниб в сочетании с пембролизумабом показали очень высо...unclassified
“…Не отмечено новых сигналов безопасности, связанных с лечением [1,14,15]. Подгрупповой анализ качества жизни (КЖ) пациентов продемонстрировал лучшую переносимость комбинации ленватиниба с пембролизумабом в сравнении с монотерапией сунитинибом, по показателям КЖ, связанного со здоровьем (Health-Related Quality of Life, HRQoL), а также по симптомам заболевания [14]. Сетевой метаанализ P. Lombardi и соавт.…”
Section: ленватиниб в сочетании с пембролизумабом показали очень высо...unclassified
“…Tedesco-Silva, H. et al compared the efficacy of everolimus and low-dose calcineurin inhibitor with standard therapy (calcineurin inhibitor and mycophenolic acid) and found that the incidence of cytomegalovirus (CMV) infection decreased significantly in patients treated with everolimus (258). Moreover, sirolimus also prevents CMV recurrence in CMV-positive kidney transplant recipients (259). Hence, mTOR inhibitor is an effective and safe therapeutic strategy in organ transplant.…”
Section: Mtor Inhibitors In Organ Transplantmentioning
confidence: 99%